Indonesia . - Heri Sugiantoro (Jurnal Al-Fatih, 2026)
This study aims to analyze the extent to which religious moderation is implemented among junior high school (SMP) students. Indonesia is a country with diverse customs, cultures, and religions, which contribute to a strong sense of moderation, particularly in religious matters. Instilling the values ??of moderation needs to be carried out comprehensively in the wider community, especially the younger generation. One strategic target for instilling the values ??of moderation is junior high schools (SMP). This research method is based on the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) guidelines. The results show that the implementation of religious moderation education in schools can be achieved through local cultural practices, namely the Pancasila Student Profile Strengthening Project (P5). Teachers and schools implement character building programs and religious activities with various methods to enable them to implement religious moderation in a society, nation, and country with diverse religions, races, and cultures.